Treatment Results for Stage III Laryngeal Cancer: Analysis of a Populational Database Using Propensity Scores - Kohler, Hugo Fontan; Carvalho, Genival Barbosa de; Kowalski, Luiz Paulo [UNESP] (Georg Thieme Verlag Kg, 2021)
Introduction Treatment of stage III laryngeal cancer suffered a major paradigm change with surgery being substituted by radiation therapy with chemotherapy. Objective To evaluate the oncological outcome of different treatment modalities for stage III laryngeal cancer using a population database. Methods A population database representing patients treated in the state of Sao Paulo, Brazil, was analyzed. Demographic, clinical and treatment variables were included, and the outcomes of interest were disease-specific and overall survival. Propensity score with nearest neighbor matching was used to compensate for imbalances in treatment groups. Results We retrieved data from 1,804 patients. In multivariate analysis, age, female gender, payment source, clinical N stage (cN) stages, and treatment modality were significant for disease-specific and overall survival. Patients submitted to surgery treatment had a significantly better disease-specific (p<0.001) and overall survival (p<0.001) compared with chemoradiation. Propensity score matching was based on cN stage, gender, age, topography, and payment modality, and allowed the pairing of 685 patients from each treatment modality. There was a significant difference in disease-specific survival favoring surgery-based treatment (p = 0.017). Conclusion The treatment choice has a significant impact on survival in patients with stage III laryngeal cancer with surgery-based treatment being superior to chemoradiotherapy (CRT).
Keywords: laryngeal neoplasms; propensity score; prognosis; surgery; radiotherapy